2017
DOI: 10.1016/j.eats.2017.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Open 4-Compartment Fasciotomy for Chronic Exertional Compartment Syndrome of the Leg

Abstract: Chronic exertional compartment syndrome (CECS) is a significant source of lower extremity pain and morbidity in the athletic population. Although endoscopic techniques have been introduced, open fasciotomy remains the mainstay of surgical treatment because of the paucity of evidence in support of an endoscopic approach. The literature on surgical management of CECS is mixed, and overall success rates are modest at best. Optimizing surgical technique, including prevention of neurovascular injury and wound compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The medial location of the neurovascular structures, which crossed the cephalad end of the planned fasciotomy path, resulted in premature discontinuation of the procedure in one case. Our starting location (approximately 2 cm posterior/lateral to the medial tibial crest, Figure 2) was chosen in part based on the starting location noted in several prior studies 12‐16 . A more anteromedial start location may have facilitated a path around the neurovascular bundle and allowed for achievement of the target distance in that cadaveric specimen.…”
Section: Discussionmentioning
confidence: 99%
“…The medial location of the neurovascular structures, which crossed the cephalad end of the planned fasciotomy path, resulted in premature discontinuation of the procedure in one case. Our starting location (approximately 2 cm posterior/lateral to the medial tibial crest, Figure 2) was chosen in part based on the starting location noted in several prior studies 12‐16 . A more anteromedial start location may have facilitated a path around the neurovascular bundle and allowed for achievement of the target distance in that cadaveric specimen.…”
Section: Discussionmentioning
confidence: 99%
“…There is a possibility of recurrence of ECS in affected compartments of about 6 to 11%, which will be evaluated for a second fasciotomy procedure 9 . Although results vary in substantial ranges, a recent systematic review on fasciotomy for ECS concluded an overall success rate of 66%, satisfaction rate of 84% as well as return to full activity of 75% 19 . Each percentage is a significant amount over 50%, which concludes it to be overall successful in each aspect.…”
Section: Diagnosis and Treatment Of Exertional Compartment Syndromementioning
confidence: 99%
“…Fasciotomy is now a standardized procedure with techniques well described in the literature. 3 , 12 The technique is reproducible, with the main risks being nerve injuries, incomplete release, or wound complications. 2 It is, therefore, our view that the failure of surgery is more likely to be related to patient selection rather than the surgical procedure itself.…”
mentioning
confidence: 99%